The Role of Museums in the Process of Creating a Brand City: The Case of Ankara - Burcu Zeybek; İlknur Doğu Öztürk (Türkiye İletişim Araştırmaları Dergisi)
It is crucial to evaluate the usage practices of social networks in sustaining the urban brand. In this study, we discussed how museums as social memory spaces are subject to social media posts. The study is noteworthy because it gives an opinion about social media posts of museum visitors and determines the approach to museums in the formation of an urban brand. Accordingly, we examined the Instagram posts of social media users related to museums in Ankara via content analysis. We found that the posts shared were mainly photos. Museums were the greatest data source for the corporate Instagram accounts according to sharing frequency and they were all foundation and private museums. Examining the purposes of sharing, we determined a multidirectional social media use in the dimensions of communication via announcement, publicity and informing. Analysing the use of hashtags related to museums in the process of creating a brand city revealed that museums highlighted themselves, their activities and the city where they are located. The experience of visiting the museum creates the opinion that there is an impression of the brand value of the city where the museum is located. As a result of the study, we found that it is necessary to organize a campaign based on a specific motto to be shared by corporate accounts of museums, personal accounts of visitors, and Instagram content creators to strengthen the positioning of Ankara museums related to the city.